If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -7) = 4(3x + 2) + 6(5x + 9) + 3 Reorder the terms: 2(-7 + 3x) = 4(3x + 2) + 6(5x + 9) + 3 (-7 * 2 + 3x * 2) = 4(3x + 2) + 6(5x + 9) + 3 (-14 + 6x) = 4(3x + 2) + 6(5x + 9) + 3 Reorder the terms: -14 + 6x = 4(2 + 3x) + 6(5x + 9) + 3 -14 + 6x = (2 * 4 + 3x * 4) + 6(5x + 9) + 3 -14 + 6x = (8 + 12x) + 6(5x + 9) + 3 Reorder the terms: -14 + 6x = 8 + 12x + 6(9 + 5x) + 3 -14 + 6x = 8 + 12x + (9 * 6 + 5x * 6) + 3 -14 + 6x = 8 + 12x + (54 + 30x) + 3 Reorder the terms: -14 + 6x = 8 + 54 + 3 + 12x + 30x Combine like terms: 8 + 54 = 62 -14 + 6x = 62 + 3 + 12x + 30x Combine like terms: 62 + 3 = 65 -14 + 6x = 65 + 12x + 30x Combine like terms: 12x + 30x = 42x -14 + 6x = 65 + 42x Solving -14 + 6x = 65 + 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. -14 + 6x + -42x = 65 + 42x + -42x Combine like terms: 6x + -42x = -36x -14 + -36x = 65 + 42x + -42x Combine like terms: 42x + -42x = 0 -14 + -36x = 65 + 0 -14 + -36x = 65 Add '14' to each side of the equation. -14 + 14 + -36x = 65 + 14 Combine like terms: -14 + 14 = 0 0 + -36x = 65 + 14 -36x = 65 + 14 Combine like terms: 65 + 14 = 79 -36x = 79 Divide each side by '-36'. x = -2.194444444 Simplifying x = -2.194444444
| 9y-32=-4(y-5) | | 4(w+3)=6w+24 | | 9y-37=5(y-9) | | 4x+9x-8x-5x=15 | | y=11+-5x | | 3(x-6)=39 | | 8-(6-6n)+9n=-2+12(n+1) | | (m^2+6m+4)(3m-1)=0 | | 9y^2+2+16=-24y | | 2x+6-x=(3x+18) | | 9y^22+16=-24y | | (w-9)*(w+4)= | | (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 | | 32x^2-332x+8=0 | | 6x+8=4(x+9) | | 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 |